THE EVOLUTION OF THE PENALTY IN THE PROVINCE OF LA PAMPA FROM PROVINCIAL AUTONOMY TO THE END OF THE 20TH CENTURY. (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The present is the second part of a paper, whose previous segment was sent to the "Perspectiva" Magazine for publication in previous issues and includes the provincial period of the province of La Pampa.The history of the criminal jurisdiction of the Judiciary of La Pampa and the impact of social actors in their transformation, are issues that almost no academic studies at the provincial level.Indeed, through a legislative compilation made, which began in 1884 and lasted until 2016, it was to make a historical reconstruction of the evolution of the provincial criminal courts; in turn, each of the structural and procedural changes that occurred over the years analyzed were related and contrasted with provincial, national and international historical events, so try to arrive at an explanation regarding the reasons why they were thereby giving rise.In this way in the analysis quantitative changes were noted according to the structural increase immunity itself, and qualitative, that were intended to ensure efficient and actual response in key access to justice; recognition and respect of rights and constitutional guarantees and conventional; due process both defendants as victims; and, ultimately, greater efficiency in managing the conflict.
Keywords: judicial branch; La Pampa; penal law; history; evolution